A review on molecular simulation application in the field of coal macromolecular structure - Cong YANG; Peng XIA; Niuniu ZOU; Huan YANG; Yin YU; Biao ZHU (Meikuang Anquan)
Constructing a macromolecular model of coal is essential for conducting in-depth investigations into a myriad of coal-related physical processes and chemical reactions. These processes include the adsorption behavior of coalbed methane (CBM), the pyrolysis mechanisms of coal, and alterations in the microscopic wettability of coal dust. Such research has profound implications for the advancement of CBM mining and the coal chemical industry. Coal is a complex polymer. The cornerstone of constructing the coal macromolecular structure model lies in developing the optimization mechanism and validation methods, which collectively form the foundation for this molecular model. This paper highlights the critical significance and merits of employing molecular simulation techniques for the construction, optimization, and validation of coal macromolecular structure models. These techniques encompass molecular mechanics, molecular dynamics, and quantum mechanics. It also analyzes recent developments in classical coal macromolecular structure models and explores the potential applications of molecular simulation in this domain.